Finland : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses key findings of fiscal transparency evaluation for Finland. It highlights that Finland meets most of the principles of the Fiscal Transparency Code at good or advanced level. Some areas, notably related to the analysis and management of fiscal risks, are still rated as basic or below, but with a few exceptions the importance of these areas for fiscal management in Finland is relatively low. Overall, the Finnish authorities produce an impressive amount of data and information related to all three pillars of the Code. It is also highlighted that fiscal reporting in Finland is transparent and meets good or advanced practice in all areas.